Pilkada and Identity Politics in Multicultural Cities: An Analysis of the 2024 Singkawang’s Local Politics Contestation - Akhmad Rifky Setya Anugrah (Politicon : Jurnal Ilmu Politik, 2025)
The local election (Pilkada) in Indonesia is increasingly revealing the influence of identity politics, especially in multicultural cities such as Singkawang. Known for its ethnic and religious diversity, comprising Chinese, Malay, Dayak, and other groups, Singkawang provides a unique arena where political competition is shaped not only by candidate competence and party platforms but also by mobilisation along identity lines. In the 2024 Pilkada, the city’s tolerant image contrasts with persistent contestations over representation and resource distribution, making identity both a tool of solidarity and a source of potential division. Examining Singkawang local politics thus offers valuable insights into how identity politics function in diverse urban settings and what this means to the trajectory of Indonesia’s democratic consolidation. This political milestone reflects the effective use of political identity strategies by parties in an inclusive civic culture. The present article employs qualitative explanatory methods. The data sources comprise in-depth interviews with a range of informants, as well as a literature study that involved exploring relevant data from various online sources, including books, journals, websites, and news portals. This study aims to explore the dynamics of local politics in Singkawang ahead of the 2024 Pilkada by examining the emergence of prospective mayoral candidates and local political issues. This study examines how political identity, particularly ethnic and religious affiliations, remains a decisive factor in shaping voter behavior and candidate strategies, reflecting both the city’s multicultural strength and its underlying political vulnerabilities. The findings are expected to contribute to the broader development of Indonesian political perspectives.